2020
DOI: 10.1016/j.gie.2020.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Fully covered self-expanding metal stents for benign biliary stricture after orthotopic liver transplant: 5-year outcomes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Therefore, the occurrence of migration during cSEMS strongly influences the risk of recurrence of the stricture, 5,[29][30][31][32] as highlighted in the data summarised in Table 4. 11,23,[33][34][35][36][37] The length of the cSEMS indwell period is not yet standardised but most authors have suggested 3-6 months. 25,38 Accordingly, to the variability of the indwell period of the cSEMS among centres, the median stent permanence is similar between the group with migration and the one without.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the occurrence of migration during cSEMS strongly influences the risk of recurrence of the stricture, 5,[29][30][31][32] as highlighted in the data summarised in Table 4. 11,23,[33][34][35][36][37] The length of the cSEMS indwell period is not yet standardised but most authors have suggested 3-6 months. 25,38 Accordingly, to the variability of the indwell period of the cSEMS among centres, the median stent permanence is similar between the group with migration and the one without.…”
Section: Discussionmentioning
confidence: 99%
“…After stenting, the stent position can adjust under endoscopic control. Studies in the literature have reported that the incidence of adult esophageal stent displacement was 37–63% 22 , 23 , and suggested the smaller the inner diameter or the closer the stent was placed to the upper or lower end of the esophagus, the more likely it was to shift position 24 . In our study, only 1 child (case 13) had stent migration 7 days after stent placement (1/14 7.1%), and we believe that the accurate evaluation of stenosis and the reasonable and scientific design of the stent is important, while special attention should be paid to the size of the upper bell mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations from the Asia-Pacific guidelines recommend the use of FCSEMS or MPS for the endoscopic treatment of CP-associated BBS[ 62 ]. To date, the WallFlex Biliary RX Fully Covered Stent (Boston Scientific, United States) is the only FCSEMS approved by the United States Food and Drug Administration for treatment of BBS due to CP for indwell time up to 12 mo[ 63 ].…”
Section: Benign Biliary Stricturesmentioning
confidence: 99%